What’s new in mesothelioma - ASCOLI, V.; MURER, B.; NOTTEGAR, A.; LUCHINI, C.; CARELLA, R.; CALABRESE, F.; LUNARDI, F.; COZZI, I.; RIGHI, L. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Malignant pleural mesothelioma is a neoplasm characterized by a very poor prognosis and medico-legal implications. Diagnosis, prognosis and therapy are often challenging and include several issues. Cytological diagnosis is frequently the first step of the diagnostic process, and although its sensitivity may be somewhat lower, diagnostic criteria should be taken into account. When effusion cytology is inconclusive for the diagnosis, tissue biopsies should be taken. Even if the morphologic criteria for deciding whether a mesothelial proliferation is a benign or a malignant process have been defined, the separation of benign from malignant mesothelial proliferation is often a difficult problem for the pathologist, particularly on small biopsies. Thirdly, when the diagnosis is made, despite many efforts have been made to identify possible new biomarkers for early diagnosis, prognostic stratification and also predictive tools should be defined. Nowadays, the main prognostic parameter is still represented by the histological subtype, having the epithelioid MPM a better outcome than the sarcomatoid or biphasic MPM. A nuclear grading system have been also proposed to stratify patient outcome. Reliable predictive biomarkers are still lacking in MPM and a personalized therapeutic concept is eagerly needed. Mesothelioma occurs mostly as sporadic cancer and the main risk factor is asbestos exposure, but it also occurs among blood relatives suggesting possible increased genetic susceptibility besides shared exposures. Recently the study of genetic predisposition syndrome raised new aspect in the occurrence of mesothelioma cases. This review summarize these most important issues.